Catcalling Di Kalangan Mahasiswa Universitas Palangka Raya Perspektif Korban Dan Pelaku Dalam Tinjauan Sosiologi - Luh Bulan Awidiyasari; Jessica Kezia Baboe; Marcellin; Osi Karina Saragih; Saputra Adiwijaya; Muhammad Zusanri Batubara (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
The phenomenon of catcalling among Palangkaraya University students in the perspective of victims and perpetrators in a sociological review. Catcalling is generally seen as trivial matters by the perpetrator, but is understood as a form of verbal sexual harassment that has a significant impact on the victim's psychology. This study used qualitative methods, data were taken from direct interviews and surveys with students from various faculties. The results showed that the perpetrators viewed catcalling as a form of joke and casual interaction, and the victims especially women, felt disturbed, uncomfortable, and even threatened. In the results of this study there are differences in responses based on gender. This study uses radical feminism theory to analyze the dynamics of power relations in a patriarchal society that allows catcalling to occur.